2012
DOI: 10.1038/aja.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

Does alcohol have any effect on male reproductive function? A review of literature

Abstract: Although alcohol is widely used, its impact on the male reproductive function is still controversial. Over the years, many studies have investigated the effects of alcohol consumption on sperm parameters and male infertility. This article reviews the main preclinical and clinical evidences. Studies conducted on the experimental animal have shown that a diet enriched with ethanol causes sperm parameter abnormalities, a number of alterations involving the reproductive tract inhibition, and reduced mouse oocyte i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 34 publications
3
86
0
7
Order By: Relevance
“…It is reported that 75% of children with fetal alcohol syndrome have fathers who were alcoholics [120]. Alcohol consumption is associated with a deterioration of sperm parameters which may be partially reversible upon alcohol consumption discontinuation [121]. Although, paternal alcohol consumption has been shown to affect the growth and behavior of the offspring, the mechanisms underlying these effects still remain to be elucidated.…”
Section: Consumption Of Alcoholmentioning
confidence: 99%
“…It is reported that 75% of children with fetal alcohol syndrome have fathers who were alcoholics [120]. Alcohol consumption is associated with a deterioration of sperm parameters which may be partially reversible upon alcohol consumption discontinuation [121]. Although, paternal alcohol consumption has been shown to affect the growth and behavior of the offspring, the mechanisms underlying these effects still remain to be elucidated.…”
Section: Consumption Of Alcoholmentioning
confidence: 99%
“…Further, caffeine intake in women prior to pregnancy has not been conclusively shown to affect fertility; however, it may increase their risk for spontaneous abortion in the first trimester (29)(30)(31). Even though there is conflicting evidence in the literature about the effects of substance use and fertility, it is recommended that men and women cease use of these substances for fertility, preconception health, and overall good health (6,17,18,21,23,24,32).…”
Section: Effects Of Substance Use On Reproductive Healthmentioning
confidence: 99%
“…Much like male fertility, evidence is not conclusive as to whether alcohol consumption has an impact on female fertility (21,22). There is evidence, however, that excessive alcohol intake in males is associated with testicular atrophy, decreased libido, erectile dysfunction, and reduced effectiveness of assisted reproductive technology (ART) procedures (17,23,24). Although the evidence was minimal, anabolic steroids and recreational drugs can cause damage to sperm, but the sperm may recover with discontinuation of use of steroids and drugs (17).…”
Section: Effects Of Substance Use On Reproductive Healthmentioning
confidence: 99%
“…A complete medical history was collected and all of them underwent a careful physical examination and laboratory and ultrasound instrumental evaluation. Men with male accessory gland infection (4), systemic diseases (5, 6), microorchidism (testicular volume <12 ml) (7), history positive for cryptorchidism (8) or varicocele (9), drug and/or alcohol use/abuse (10), and recent «12 months) hormonal treatments were excluded. The protocol was approved by the internal Institutional Review Board and an informed written consent was obtained from each patient.…”
Section: Methodsmentioning
confidence: 99%